TANGGUNG JAWAB SOSIAL MASYARAKAT PINGGIRAN SUNGAI DALAM PENGELOLAAN SAMPAH PERSPEKTIF KEWARGANEGARAAN EKOLOGIS DI DESA ALUH-ALUH BESAR KECAMATAN ALUH-ALUH - Puteri, Nispia; Mariatul Kiptiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Aluh-Aluh Besar Village is a village in Aluh-Aluh District, Banjar Regency, South Kalimantan Province, where most of the settlements are located along the riverbanks. Rivers play an important role as a source of life, a means of daily activities, and a supporter of the community's economy. However, waste management remains a serious problem because some people still dispose of household waste directly into the river. This condition reflects a low level of social responsibility towards the environment from an ecological citizenship perspective. This study aims to determine the behavior and moral social responsibility of riverbank communities in waste management and the factors that influence it. The study used a qualitative approach with observation, interview, and documentation techniques, as well as analysis through data reduction, data presentation, and drawing conclusions. The results show that community behavior in waste management is still not optimal, characterized by the habit of throwing waste into the river due to the proximity of settlements and limited facilities. Morally, the community has an awareness of maintaining cleanliness and understands the importance of waste management, but this has not been fully implemented in real behavior. Influencing factors include awareness that is defeated by habit, limited facilities, the lack of village government involvement, and the influence of the social environment. Therefore, it is necessary to increase awareness, provide facilities, and collaborate between the government and the community.